Algorithms of common solutions for a fixed point of hemicontractive-type mapping and a generalized equilibrium problem - Zegeye, Habtu; Hadush Meche, Tesfalem; Goa Sangago, Mengistu (International Journal of Advanced Mathematical Sciences, 2017)
In this paper, we introduce and study an iterative algorithm for finding a common element of the set of fixed points of a Lipschitz hemicontractive-type multi-valued mapping and the set of solutions of a generalized equilibrium problem in the framework of Hilbert spaces. Our results improve and extend most of the results that have been proved previously by many authors in this research area.